Racionalidade tecnológica: Marcuse e a crítica da sociedade industrial avançada - Santos, Edjeverson Bezerra (2019)
This work will reflect about Marcuse conception of the technical / technology theme as well as its consequences in the late capitalism. The primary issue is the announcement of the release of alienated labor through the development of productive forces and consequently the constant production automation in advanced capitalist societies. What is denounced is the close relationship between science and capital at the expense of individual, which in turn, from the development of science and technology secure, through the conditions of consumption and increasing productivity in a subordinate position opposite the technological apparatus. The interpretation of Marcuse on the subject technology does not occur in a Manichean way, in other words, categorically good or bad. The kernel of the problem lies in the way science is developed and implemented in societies of late capitalism.